Fracturing failure simulations of rock discs with pre-existing cracks by numerical manifold method. (March 2023) - Ning, Youjun; Lu, Qi; Liu, Xinlian
Abstract: Diametral compression of disc-like specimens with pre-existing cracks is widely used in the study of rock fracturing failures. In the present study, a unified numerical method, namely, numerical manifold method (NMM), is further enhanced for better simulations of rock cracking by effectively considering the friction on the new crack surfaces. Simulations of disc and semi-disc specimens with a single pre-existing crack of different inclinations prove that the improved NMM can reproduce the crack development path which agrees better with the theoretical and experimental results. Thereafter, disc specimens with vertically or horizontally distributed parallel pre-existing cracks of different numbers and distances are simulated, respectively. The derived fracturing failure patterns of the discs match the corresponding results by other numerical methods or physical experiments well. The NMM simulations also indicate that the increase of the pre-existing crack number will reduce the strength of the disc, but the number of the vertically distributed pre-existing cracks shows a much more obvious influence. Meanwhile, the increase of the pre-existing crack distance will increase the strength of the disc with horizontally distributed pre-existing cracks, while the pre-existing crack distance shows a nonmonotonic influence on the disc strength for discs with vertically distributed cracks.